2021
DOI: 10.3389/fimmu.2021.696784
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Modulation of Transient Receptor Potential Channels: An Unmet Therapeutic Intervention for Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a multifaceted, chronic relapsing inflammatory skin disease that affects people of all ages. It is characterized by chronic eczema, constant pruritus, and severe discomfort. AD often progresses from mild annoyance to intractable pruritic inflammatory lesions associated with exacerbated skin sensitivity. The T helper-2 (Th2) response is mainly linked to the acute and subacute phase, whereas Th1 response has been associated in addition with the chronic phase. IL-17, IL-22, TSLP, and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 190 publications
(233 reference statements)
0
56
0
2
Order By: Relevance
“…Our results also indicated the presence of a truncated transcript of TRPA1 in immune cells, similarly to that reported in Supplemental Data Figure S1 by Bautista et al for TRG tissue of the same strain of TRPA1 functional deficient KO mice [58]. Expression of TRPA1 mRNA and protein in immune cells was reported based on comprehensive expression profile analysis of TRP channel gene families including TRPA1 in immune organs [89], end-point RT-PCR analysis, immunostaining by Western blot and other techniques or by functionality analysis in mouse immune cells, e.g., CD4+ splenocytes [7], in Th2 type T cells [44]. However, the levels of mRNA and protein expression have not been completely clarified by comparison to that of primary sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also indicated the presence of a truncated transcript of TRPA1 in immune cells, similarly to that reported in Supplemental Data Figure S1 by Bautista et al for TRG tissue of the same strain of TRPA1 functional deficient KO mice [58]. Expression of TRPA1 mRNA and protein in immune cells was reported based on comprehensive expression profile analysis of TRP channel gene families including TRPA1 in immune organs [89], end-point RT-PCR analysis, immunostaining by Western blot and other techniques or by functionality analysis in mouse immune cells, e.g., CD4+ splenocytes [7], in Th2 type T cells [44]. However, the levels of mRNA and protein expression have not been completely clarified by comparison to that of primary sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression and functions has been described in various non-neuronal cells [1,43] such as keratinocytes [44], vascular smooth muscle cells [45], dendritic cells [46] in the gut [7,47], skin [48,49] and lungs [50], in peripheral blood leukocytes [14], in monocytes and macrophage-derived cell lines [51,52] and in lymphocytes, including CD4+ T cells [7,53]. However, both the level of expression and the role of TRPA1 in immune cells is still not unambiguously clear, primarily because of the controversial specificity of the applied antibodies [54], and the existence and regulatory effects of mouse and human TRPA1 splice variants [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of these receptors leads to the activation of the immune response as well as the accumulation of pro-inflammatory cytokines, chemokines and antibacterial proteins. In the acute phase of AD, it is observed that stimulated dendritic cells activate naive T cells in the regional lymph nodes, with the consequent proliferation of Th2 lymphocytes which return to the skin to produce pro-inflammatory cytokines; interleukins (IL4, IL5, IL13), this process causes the development of inflammation [57,59].…”
Section: The Microbiome and Its Role In Atopic Skin Inflammationmentioning
confidence: 99%
“…TRPV3, activated by warm temperatures (> 32° C), was abundantly expressed in skin keratinocytes, not in rodent but in human sensory (DRG) neurons, and accordingly, from knockout mice no alterations in thermal preference and noxious heat withdrawal were reported [79]. TRPV3 found great attention in dermatology, a human gain-of-function mutation is in part responsible for the hyperkeratotic and mutilating Olmsted syndrome; TRPV3 plays roles in the control of hair growth and lipid secretion, in atopic dermatitis and pruritus [91,107]. However, by optogenetic inhibition of keratinocytes in mice, it was recently shown that stimulated ATP release from these cells contributes to behavioural heat, cold, and mechanosensitivity through neuronal P2X4 purinoceptor channels [109,147], and TRPV3 expression is essential for the heat-induced ATP release that is able to activate nearby DRG neurons in co-culture with keratinocytes [103].…”
Section: Price Worthy Trps Trpv3 and Trpm8mentioning
confidence: 99%